Scalp malignant trichilemmal tumour with bony erosion: a new clinical entity. Issue 5 (10th May 2021) - Virdi, Amrita; Borghol, Khaled; Edwards, Bethan; Barnard, Neal
Abstract : Trichilemmoma is a benign tumour which arises from the hair follicle root sheath, and commonly occurs in the head and neck area. Malignant transformation and locally aggressive growth of these tumours are very rare. Surgical excision remains the mainstay of management, with scarce evidence for other treatment modalities. We describe our experience of a malignant trichilemmal tumour which demonstrated bony erosion with intracranial extension. Our patient was treated with radical radiotherapy, with a good response at 6 months of follow-up. This case highlights the need to consider malignant potential in recurrent skin lesions, along with the potential for trichilemmoma to erode bone, necessitating the consideration of different treatment modalities.